2022
DOI: 10.1136/bmjdrc-2022-002777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TRAM-34 and minocycline on neuroinflammation caused by diabetic ketoacidosis in a rat model

Abstract: IntroductionDiabetic ketoacidosis (DKA) causes acute and chronic neuroinflammation that may contribute to cognitive decline in patients with type 1 diabetes. We evaluated the effects of agents that reduce neuroinflammation (triarylmethane-34 (TRAM-34) and minocycline) during and after DKA in a rat model.Research design and methodsJuvenile rats with DKA were treated with insulin and saline, either alone or in combination with TRAM-34 (40 mg/kg intraperitoneally twice daily for 3 days, then daily for 4 days) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Diabetes is a multisystem disease, and advanced, untreated diabetes may lead to diabetic ketoacidosis and thus neuroinflammation. Although a study on rats has not shown elevated brain concentrations of the rat equivalent of CXCL1 during diabetic ketoacidosis [90], the link between diabetes, neuroinflammation and CXCL1 needs to be investigated in a human model.…”
Section: Diabetesmentioning
confidence: 99%
“…Diabetes is a multisystem disease, and advanced, untreated diabetes may lead to diabetic ketoacidosis and thus neuroinflammation. Although a study on rats has not shown elevated brain concentrations of the rat equivalent of CXCL1 during diabetic ketoacidosis [90], the link between diabetes, neuroinflammation and CXCL1 needs to be investigated in a human model.…”
Section: Diabetesmentioning
confidence: 99%
“…The administration of mitochondrial uncouplers to mice with TBI significantly restored cognitive function by reducing oxidative stress and hippocampal cell death [7]. Inflammation Cytokines are elevated in the plasma of diabetic patients, thereby activating microglia, causing central inflammation, and accelerating cognitive dysfunction [16,17] Ferroptosis Downregulation of SLC40A1 leads to ferroptosis in the brain and subsequent cognitive dysfunction in diabetes [18] DKA CBF Cerebral edema is associated with regional CBF abnormalities in children with DKA [21] Inflammation DKA induces acute systemic inflammation and chronic neuroinflammation [22] High cholesterol Inflammation and BBB dysfunction HCD induces severe astrogliosis and decreases tight junction protein expression [23] Inflammation and cerebral microcirculation HCD induces cerebral vasodilator dysfunction and upregulates galectin-3 immunoreactivity in microglia [24] Inflammation and abnormal protein deposition HCD activates microglia and accelerates Aβ accumulation and tau phosphorylation [25] a Abbreviations: BDNF, brain-derived neurotrophic factor; BMVECs, brain microvascular endothelial cells; HCD, high-cholesterol diet; ICAM, intercellular cell adhesion molecule; PDGF-Rβ, platelet-derived growth factor receptor beta; SLC40A1, solute carrier family 40 member 1; VCAM, vascular cell adhesion molecule.…”
Section: Box 1 Main Mechanisms Of Cognitive Dysfunction After Tbimentioning
confidence: 99%
“…Cognitive impairment is closely related to the severity of DKA [20]. Although the mechanism by which DKA induces cognitive impairment is unclear, it may be caused by altered cerebral blood flow (CBF) [21] and neuroinflammatory responses [22] (Table 1). Although DKA has been demonstrated to play an important role in cognitive function in children, there are few studies on the relationship between DKA and cognitive impairment.…”
Section: Open Accessmentioning
confidence: 99%
“…In the original study by Glaser of rat models, DKA caused acute systemic inflammation, including neuroinflammation. Importantly, the neuroinflammatory response induced by DKA was long-lasting, suggesting that DKA may contribute to long-term cognitive decline in patients with diabetes [62]. Although the underlying mechanisms remained to be elucidated, as a serious complication of hyperglycemia, it was suggested that DKA played an important in diabetes-related cognitive decline.…”
Section: Diabetic Ketoacidosis (Dka)mentioning
confidence: 99%